2016
DOI: 10.1055/s-0036-1582226
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography in Multiple Sclerosis

Abstract: Retinal optical coherence tomography (OCT) has recently become a vital tool for clinicians and researchers in ophthalmology and, increasingly, in neurology. Optical coherence tomography is quickly and easily performed, well-tolerated by patients, and allows high-resolution viewing of unmyelinated axons and other retinal structures in vivo. These factors have led OCT to find favor as a method of quantifying neuroaxonal loss in multiple sclerosis (MS), and the increasing acceptance of the anterior visual pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
(135 reference statements)
1
3
0
Order By: Relevance
“…Moreover, it has been demonstrated that MS patients not experiencing ON show a significant retinal atrophy, confirmed by lower retinal thickness at OCT after six months; the same pattern is shared by subclinical ON or primary retinal degeneration and neurodegeneration processes [27,34,40,41,42]. In our study, retinal measurements of the unaffected eyes showed a significant reduction of RNFL thickness with particular involvement of the nasal and temporal quadrants (Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, it has been demonstrated that MS patients not experiencing ON show a significant retinal atrophy, confirmed by lower retinal thickness at OCT after six months; the same pattern is shared by subclinical ON or primary retinal degeneration and neurodegeneration processes [27,34,40,41,42]. In our study, retinal measurements of the unaffected eyes showed a significant reduction of RNFL thickness with particular involvement of the nasal and temporal quadrants (Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…For instance, axonal loss documented with OCT correlates with functional changes measured using electrophysiological techniques. Therefore, assessment of the retinal nerve fibre layer provides a gateway to understanding the anterior neural pathway of this neurodegenerative process occurring in the brain and spinal cord.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…A significant relationship between OCT parameters and electrophysiological tests such as the visual evoked potential (VEP) and ERG has been observed in multiple sclerosis [61]. VEP and ERG examinations are performed in order to quantify the cortical (VEP) and retinal (ERG) response to precisely defined visual stimuli [62].…”
Section: Clinical Relevance Of Optical Coherence Tomography Findings mentioning
confidence: 99%